The Relationship of Learning Based on Three-Dimensional Visual Media (3D) with the Critical Thinking Skills of Students in Mathematics Learning in Public Elementary Schools - komang Yudakarsana; Ujang Efendi; Rochmiyati Rochmiyati (Program Studi Magister Manajemen Pendidikan)
Abstract: The Relationship of Learning Based on Three-Dimensional Visual Media (3D) with the Critical Thinking Skills of Students in Mathematics Learning in Public Elementary Schools. The problem of this research is the low critical thinking skills of students in learning mathematics. The purpose of this study was to see the critical thinking skills of students when learning using three-dimensional (3D) visual media and to find out the relationship between visual three-dimensional (3D) based learning and students' critical thinking skills in mathematics learning at SD Negeri 3 Perumnas Way Kandis.. This type of research is correlational research with a quantitative approach. The population numbered 195 and the study sample numbered 60 students. Data collection techniques used were questionnaire and documentation. The results of the study, it was found that there is a positive and significant relationship between learning based on three-dimensional visual media (3D) with students' critical thinking skills in mathematics learning with